A case of highly suspected small cell osteosarcoma in the mandible. Issue 1 (January 2015) - Harazono, Yosuke; Yamashiro, Masashi; Yoshitake, Hiroyuki; Kayamori, Kou; Izumo, Toshiyuki; Harada, Kiyoshi
Abstract Osteosarcoma (OS) in the jaw is rare, accounting for 4–6% of all OS. Small cell osteosarcoma (SCO), which is the rarest of the several subtypes of OS, accounts for about 1.5% of all OS. To the best of our knowledge, only three cases of SCO in the jaw have been reported previously in the literature. We report here a case of SCO in the left mandible of a 26-year-old female, which was successfully treated with surgery and postoperative chemotherapy. This case suggested that differential and confirmed diagnoses of SCO were difficult.